The Determinants of the Performance of Commercial Banks Industry Evidence of Listed Commercial Banks at ADX - MOHAMMAD YASSEN DARKAL, MOHAMMAD YASSAR (2018)
I would like to express my heartfelt gratitude for the support and encouragement of numerous people whose contributions were important for me along the period of master program. The greatest goes to my God who enable me to fulfil the requirements of my master’s degree, and enabled me to overcome the obstacles that faced me at several stages of the program. Dr. Abdul Muneam Lhrech, my supervisor, provided me with enough help, and encouraged me with different guides, regulations, experience, and high quality of direct face to face supervision. Therefore, a lot of thanks and acknowledgements to Dr. Lahrech. I will not forget the help, support and quality of supervision that I received from Dr. Husam Malkawi. The current study objects for determining the factors that are probably influencing the performance of listed commercial banks at Abu Dhabi Securities Exchange (ADX). To achieve this objective, the data covering the period 2008-2017, of 8 listed commercial banks among 12 listed bank banks At ADX. The study investigated 5 internal-based possible determinants, and three potential external determinants of commercial banks performance. Among the 12 listed banks at ADX, 2 commercial banks had excluded because its data is not available in complete along the period of the study, and another 2 Islamic banks had also excluded because the nature of operations in these banks is completely different, and therefore the financial reporting of this type of banks is also different, where this restrict the analysis of data. As a result of the related literature and prior researches consideration, 9 hypotheses had been developed and scientifically tested. In addition to simple linear regression method that used in hypotheses testing, correlation and some descriptive statistics were also applied in the analysis of data. The findings demonstrate that except inflation rate and GDP, all other determinants have a significant effect on bank performance. In other words, it demonstrates that all internal determinants that had been taken into account, found affecting commercial bank performance, and two of external determinants have no effect. The eight determinants of commercial banks that the study takes into consideration, include, bank loans, bank size, capital adequacy, management efficiency, bank liquidity, inflation rate, GDP, and Tobin’s Q. Five of these determinants are classified by some authors as in internal including, bank loans, bank size, capital adequacy, management efficiency, and bank liquidity, while inflation rate, GDP, and Tobin’s Q, are classified as external. The study recommends managements of commercial banks to give more attention to the assets used in these banks, and to focus on increasing the market value of commercial banks. In addition, managements of commercial banks are recommended to give more attention to the way that liquid assets and credit risk are managed.